Team-teaching as a tool for professional development - insiders' views = Dạy cặp như một phương tiện phát triển nghề nghiệp: quan điểm của người tham gia. M.A Thesis Linguistics: 60 14 10 - Trần, Kim Tú (University of Languages and International Studies, 2017)
With the development of regional integration and global participation, the quality of education is becoming an urgent need to the Ministry of Education and Training as well as the government. Since the Vietnamese government sees the quality of teachers as the major factor in improving education, it is setting targets for the general reform of cirriculum and teaching methods in all educational establishments. The study was conducted to explore the team-teachers' viewpoints and attitudes towards team-teaching in order to find out the benefits of team-teaching in terms of their professional development as well as the barriers to team-teaching. From the findings of the study, some recommendations were proposed for the administrator and team-teachers so as to use team-teaching as an effective means of professional development.